Multistate unfolding of alpha-mannosidase from Canavalia ensiformis (Jack Bean): evidence for the thermostable molten globule - Kumar, Avinash; Gaikwad, Sushama M. (Biochemical and Biophysical Research Communications, 2010)
The relevance of partially ordered states of proteins (such as the molten-globule state) in cellular processes is beginning to be understood. We examined the conformational transitions in a multimeric and high molecular weight class II alpha-mannosidase from Canavalia ensiformis (Jack Bean) (Jb alpha-man) utilizing intrinsic fluorescence, solute quenching, hydrophobic dye binding, size exclusion chromatography and circular dichroism (CD) spectroscopy for the protein in presence of Guanidine hydrochloride (GdnHCl). The decomposition analysis of the protein spectra obtained during unfolding showed progressive appearance of class S, I, II and III trp. The parameter A and spectral center of mass showed multi state unfolding of the protein and phase diagram analysis revealed formation of an intermediate of Jb alpha-man in the vicinity of 1 M GdnHCl. The intermediate exhibited compact secondary and distorted tertiary structure with exposed hydrophobic amino acids on the surface, indicating the molten-globule nature. The dissociation, partial unfolding and aggregation of Jb alpha-man occurred simultaneously during chemical denaturation. The molten-globule possessed slightly higher hydrodynamic radius, perturbance in the structure up to 60 degrees C and stability of the structure up to 80 degrees C unlike the native Jack Bean alpha-mannosidase. The modes of chemical and thermal denaturation of the native protein were different. The solute quenching parameters confirmed the altered confirmation of the intermediate. Taken together, our results constitute one of the early reports of formation of GdnHCl induced molten globule in a class II alpha-mannosidase. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: alpha-Mannosidase; Circular dichroism; fluorescence; Guanidine hydrochloride; Molten globule; Thermostability; Unfolding

Jack bean alpha-mannosidase (Jb alpha-man): tolerance to alkali, chelating and reducing agents and energetics of catalysis and inhibition - Kumar, Avinash; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2011)
Investigations of the catalytic and structural transitions of jack bean alpha-mannosidase (Jb alpha-man) are described in the present paper. The enzyme was maximally stable at pH 5.0; however, when incubated in the pH range of 11.0-12.0, showed 1.3 times higher activity and also stability for longer time. The free amino group at or near the active site was probably involved in the stability and activation mechanism. The active site is constituted by the association of two unidentical subunits connected by disulfide linkages. The metalloenzyme has Zn(2+) ions tightly bound and chelation reduces the thermal stability of the protein. Energetics of catalysis and thermodynamics of inhibition of the enzyme were also carried out. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alkali tolerance; alpha-Mannosidase; beta-Mercaptoethanol; Energetics; Inhibition; Metalloenzyme

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.